Manejo de mezclas de cultivares de musas spp para minimizar la severidad de sigatoka negra en plátano en la zona de El Carmen, Manabí. - Verdesoto Sabando, Ronny David (2016)
The handling of mixtures of cultivars Musas spp to minimize the severity of black sigatoka in banana conducted to determine optimum handling of mixtures of cultivars Musas spp order to reduce the severity of black Sigatoka and black weevil in banana studying the development of Black Sigatoka and incidence of black weevil in different intraspecific mixtures of Musa spp order to propose alternatives for integrated management of pests and diseases in banana cultivation through the use of mixtures of cultivars with different resistance levels to measure the relationship between climatic parameters and the development of black Sigatoka and incidence of black weevil. The research was conducted in the Root Complex, located in the canton of El Carmen, Manabi Province. Corresponds to a plantation established in 2012, the design of randomized complete block was applied, consisting of 3 replications and 16 treatments were statistically analyzed by Tukey test (p ≤ 0.05) for statistical significance. The variables used are the incidence of black Sigatoka, levels of black weevil damage, nematode damage and performance. According to the results reached the following conclusions: The management of intraspecific mixtures of Musa spp, did not represent any problems in terms of agronomic management, or significant differences were observed in the physiology of the different participants cultivars in mixtures, it is possible to visualize the effect of biodiversity through the use of intraspecific mixtures reducing pests and diseases, when mixtures with resistant varieties were used, as in the case of Limeño and Orito cultivars, in the case of nematodes apparently no effect was achieved noteworthy, since both mixtures and monocultures, the economic threshold allowed populations of the four most important nematodes of Musa H. multicinctus, R. similis, P. coffeae and M. hapla was exceeded, was not observed a direct relationship between climatic parameters and severity of the weevil (Cosmopolites sordidus) and the incidence of black Sigatoka (Mycosphaerella fijiensis).